Система категоріювання туристичних маршрутів та їх маркування в рамках функціональних можливостей ГІС - Сологуб, Юрій Іванович; Рудєв, Ігор Миколайович (Економіка та суспільство, 2024)
В статті розкрито підходи до класифікації (категоріювання) туристичних маршрутів відповідно до наявності в їх структурі різнотипних перешкод та визначальних факторів. Класифікація проводиться відповідно до складності наявних перешкод, району здійснення походу, ступеня автономності, унікальності та протяжності. Розвиток спортивного туризму за рахунок появи нових способів пересування в навколишньому середовищі, покращенні спорядження та широкому використанні цифрових засобів комунікації та орієнтування в просторі зумовить появу нових видів туризму та призведе до розширення існуючої класифікації туристичних маршрутів. Активне використання різнотипних геоінформаційних систем значно розширює можливості організації туристичних походів та проведення змагань з визначених видів спортивного туризму. Базовими перевагами використання цифрового картографічного продукту геоінформаційних систем є його поліфункціональність та інтерактивність по відношенню до запитів туристів під час проходження маршруту в рамках туристичного походу.

The article describes approaches to the classification (categorization) of tourist routes according to the presence of different types of obstacles and determining factors in their structure. Today, the basis of the classification of routes is the Unified All-Ukrainian sports classification (categorization) of tourist routes, which outlines the main principles, requirements and algorithm for the classification of various types of sports routes and defining obstacles according to the types of sports tourism. Classification (categorization) is carried out according to the complexity of the existing obstacles, the region (region) of the hike, the degree of autonomy, uniqueness, length and a set of other determining factors depending on the type of sports tourism. Tourist routes, depending on their belonging to one or another type of tourism, are divided into: pedestrian, water, mountain, ski, bicycle, etc., and can have the status of combined, representing a combination of different types. The active use of various types of geoinformation systems significantly expands the possibilities of organizing tourist trips and holding competitions in certain types of sports tourism. It is the digital cartographic product of modern geoinformation systems that can provide comprehensive and diverse information within the framework of the implementation of tourist trips of a high category of complexity. The following areas of use of geoinformation systems in modern sports tourism are relevant: planning of various types of tourist routes; spatial orientation and map marking of routes; training and advanced training of tourists. The basic advantages of using a digital cartographic product of geoinformation systems are its multi-functionality and interactivity in relation to tourists' requests during the route as part of a tourist trip.
Keywords: кафедра туристичного та готельного бізнесу; спортивний туризм; маршрут; категорія складності; класифікація; маркування; ГІС; sports tourism; route; difficulty category; classification; marking; GIS